An Experimental Study of Intermittent Heating Frequencies From Wind-Driven Flames - Tang, Wei; Finney, Mark; McAllister, Sara; Gollner, Michael (Frontiers in Mechanical Engineering, 2019)
An experimental study was conducted to understand the intermittent heating behavior downstream of a gaseous line burner under forced flow conditions. While previous studies have addressed time-averaged properties, here measurements of the flame location and intermittent heat flux profile help to give a time-dependent picture of downstream heating from the flame, useful for understanding wind-driven flame spread. Two frequencies are extracted from experiments, the maximum flame forward pulsation frequency in the direction of the wind, which helps describe the motion of the flame, and the local flame-fuel contact frequency in the flame region, which is useful in calculating the actual heat flux that can be received by the unburnt fuel via direct flame contact. The forward pulsation frequency is obtained through video analysis using a variable interval time average (VITA) method. Scaling analysis indicates that the flame forward pulsation frequency varies as a power-law function of the Froude number and fire heat-release rate, . For the local flame-fuel contact frequency, it is found that the non-dimensional flame-fuel contact frequency remains approximately constant before the local Rix reaches 1, e.g., attached flames. When Rix>1, decreases with local as Rix flames lift up. A piece-wise function was proposed to predict the local flame-fuel contact frequency including the two Rix scenarios. Information from this study helps to shed light on the intermittent behavior of flames under wind, which may be a critical factor in explaining the mechanisms of forward flame spread in wildland and other similar wind-driven fires.